2020
DOI: 10.1111/ijd.15081
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse events in patients receiving anticancer therapy in a tertiary hospital setting: the old and the new

Abstract: Background Targeted therapies and immunotherapies are increasingly prescribed, but classic chemotherapy agents are still highly used in cancer treatment. Both therapies, the old and the new, are associated with cutaneous adverse events (CAEs) that can cause treatment interruptions or reduce the quality of life of patients. Methods An observational, cross‐sectional, single‐center study that included consecutive cancer patients presenting CAEs. The main objective was to describe CAEs derived from antineoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In particular, anticancer therapy-related cutaneous AEs are linked to skin barrier dysfunction, which generally arises from altered proliferation and differentiation of keratinocytes but can also occur as a result of disturbances to the sebaceous glands and/or cutaneous immune system [1][2][3][4][5]. Xerosis, which is characterized by dry, rough, cracked, and fissured skin, is among the most frequent skin reactions induced by anticancer treatments [6][7][8][9][10]. This skin condition is associated with significant psychosocial morbidity and impaired quality of life (QoL) due to symptoms (itching, sleep disturbance, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In particular, anticancer therapy-related cutaneous AEs are linked to skin barrier dysfunction, which generally arises from altered proliferation and differentiation of keratinocytes but can also occur as a result of disturbances to the sebaceous glands and/or cutaneous immune system [1][2][3][4][5]. Xerosis, which is characterized by dry, rough, cracked, and fissured skin, is among the most frequent skin reactions induced by anticancer treatments [6][7][8][9][10]. This skin condition is associated with significant psychosocial morbidity and impaired quality of life (QoL) due to symptoms (itching, sleep disturbance, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pain, pruritus, dryness, swelling, and numbness caused by skin ADRs could make patients physically uncomfortable, resulting in limited physical activity; moreover, the symptoms produced by skin ADRs could hurt patients psychologically, and detrimentally affect their self-esteem and mental health. Importantly, with the increase in psychological distress, patients tend to show a desperate and evasive attitude when coping with skin ADRs 23,24 . Other studies had shown that skin ADRs could make patients feel rejected and ashamed, leading to patients' social participation barriers (social avoidance and isolation) and reduced self-identity 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the observational study on the spectrum of dermatological conditions in patients receiving anticancer therapy 1 . Oncodermatologists often have to manage the diverse cutaneous adverse effects of chemotherapy, which as Suh et al .…”
mentioning
confidence: 99%
“…Oncodermatologists often have to manage the diverse cutaneous adverse effects of chemotherapy, which as Suh et al . have explored in the article , can have a significant effect on not only skin and mucosal membranes but also affect hair and nail 1 . This can be further compounded by complications of other concurrent treatments such as radiotherapy (e.g., dermatitis and ulceration) and surgery (e.g., complex wounds).…”
mentioning
confidence: 99%